Bitter taste receptor agonists elicit G‐protein‐dependent negative inotropy in the murine heart. Issue 10 (1st July 2014) - Foster, Simon R.; Blank, Kristina; Hoe, Louise E. See; Behrens, Maik; Meyerhof, Wolfgang; Peart, Jason N.; Thomas, Walter G.
Abstract : G‐protein‐coupled receptors (GPCRs) are key mediators in cardiovascular physiology, yet frontline therapies for heart disease target only a small fraction of the cardiac GPCR repertoire. Moreover, there is emerging evidence that GPCRs implicated in taste (Tas1r and Tas2rs) have specific functions beyond the oral cavity. Our recent description of these receptors in heart tissue foreshadows a potential novel role in cardiac cells. In this study, we identified novel agonist ligands for cardiac‐Tas2rs to enable the functional investigation of these receptors in heart tissue. Five Tas2rs cloned from heart tissue were screened against a panel of 102 natural or synthetic bitter compounds in a heterologous expression system. We identified agonists for Tas2r108, Tas2r137, and Tas2r143 that were then tested in Langendorff‐perfused mouse hearts (from 8‐wk‐old male C57BL/6 mice). All Tas2r agonists tested exhibited concentration‐dependent effects, with agonists for Tas2r108 and Tas2r137, leading to a 40% decrease in left ventricular developed pressure and an increase in aortic pressure, respectively. These responses were abrogated in the presence of Gα1 and Gβγ inhibitors (pertussis toxin and gallein). This study represents the first demonstration of profound Tas2r agonist‐induced, G protein‐dependent effects on mouse heart function.—Foster, S. R., Blank, K., See Hoe, L. E., Behrens, M., Meyerhof, W., Peart, J. N., Thomas, W. G., Bitter taste receptor agonists elicit G‐protein‐dependent negative inotropy in the murine heart. FASEB J. 28, 4497–4508 (2014). www.fasebj.org